Instability of spin glass phase in divalent iron phosphate glass under a magnetic field. (14th November 2016) - Nakatsuka, Yuko; Murai, Shunsuke; Fujita, Koji; Tanaka, Katsuhisa
Abstract: The spin glass behaviour of 50FeO · 50P2 O5 (in mol%) glass has been examined under finite magnetic fields. The Sherrington–Kirkpatrick (SK) model, i.e. the mean field theory, is unsuitable for the interpretation of the frequency dependence of the ac magnetic susceptibility observed under an external field of 0.1 T; the critical exponent derived from the SK model is unphysically large. On the other hand, the droplet model explains well the frequency and field dependence of the spin-freezing temperature and the exponent of the thermally activated process is within the range defined by the droplet model. The results indicate that the spin glass phase of the 50FeO · 50P2 O5 glass is unstable against magnetic fields.